2015
DOI: 10.1007/s11099-015-0106-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of brassinosteroid and brassinosteroid mimic on photosynthetic efficiency and rice yield under heat stress

Abstract: Brassinosteroids (BRs) have been reported to counteract various stresses. We investigated effects of exogenously applied brassinosteroid, 24-epibrassinolide (EBR), and brassinosteroid-mimic compound, 7,8-dihydro-8-20-hydroxyecdysone (DHECD), on the photosynthetic efficiency and yield of rice (Oryza sativa L. cv. Pathum Thani 1) under heat stress. Solutions (1 nM) of EBR and DHECD were separately sprayed onto foliage of individual rice plants during their reproductive stage. Five days after the application, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 46 publications
9
31
0
Order By: Relevance
“…Rajasekar et al (2016) observed a reduction in the photosynthetic pigments of Zea mays plants after a water deficit. Corroborating our study, Thussagunpanit et al (2015b) observed increases in Chl a, Chl b, total chl and Car after the application of EBR to Oryza sativa plants subjected to heat stress (47°C) for 7 days.…”
Section: Discussionsupporting
confidence: 88%
“…Rajasekar et al (2016) observed a reduction in the photosynthetic pigments of Zea mays plants after a water deficit. Corroborating our study, Thussagunpanit et al (2015b) observed increases in Chl a, Chl b, total chl and Car after the application of EBR to Oryza sativa plants subjected to heat stress (47°C) for 7 days.…”
Section: Discussionsupporting
confidence: 88%
“…In eggplant seedlings exposed to 43/38 °C for 8 d, pretreatment with 0.1 μM 24-epibrassinolide increased the content of chlorophyll a, b, and (a+b) by 17, 27, and 20 %, respectively, compared to heat-exposed plants that were not BR-treated (Wu et al 2014b). The decrease in chlorophyll content was milder in rice supplemented with 24-epibrassinolide prior to exposure to 40/30 °C for 7 d relative to the control (Thussagunpanit et al 2015a). In another study, this rice cultivar treated with 24-epibrassinolide showed an increase in the content of chlorophyll a, b, and (a+b) and carotenoids by 86, 74, 83, and 28 %, respectively, on the 7 th day of a high temperature exposure, compared to plants that were not treated with BR (Thussagunpanit et al 2015 b).…”
Section: Photosynthetic Pigmentsmentioning
confidence: 92%
“…In the same cultivar grown in the field during the hot season, 24-epibrassinolide increased the total soluble sugar content in the straw (by 107 %). The hormone also increased reducing sugar content in the straw (by 72 %) and the starch content in the straw (by 27 %), husk (by 24 %), and seeds (by 35 %) (Thussagunpanit et al 2015a). Another rice cultivar exposed to a temperature of 35/32 °C for 12 h also demonstrated a decrease in the content of soluble sugars, which was further reduced by a mixture of plant growth regulators containing BRs (Fahad et al 2016).…”
Section: Sugar Accumulationmentioning
confidence: 93%
See 1 more Smart Citation
“…Earlier studies showed that BR significantly increase yield and yield components of mustard plant [ 6 ]. Foliar application and seed treatments of BR significantly enhanced growth of tomato, as well as number of fruits and weight per plant; the yield of pear and yellow passion fruit are also improved by BR application [ 64 , 65 ]. Previous studies reported that BR played a positive role in fruit ripening and fruit growth of mango, and in the quality of pitaya [ 64 , 66 ].…”
Section: Physiological Mechanisms Of Br In Plants Under Stress Conditmentioning
confidence: 99%